Formação política: um estudo com estudantes de licenciatura em educação física da Universidade Federal do Recôncavo da Bahia (UFRB) - Gibaut, Hallana Ferreira (2019)
This dissertation conducts a study about the political formation of future teachers of the Licentiate Course in Physical Education of the Federal University of Recôncavo da Bahia (UFRB). Its general objective is to identify which conceptions of political formation emerge from the process of teacher training of the Undergraduate Degree in Physical Education of UFRB / CFP, present through the reports of the students, and in a complementary way, aimed at the following specific objectives: To investigate if the student has reflected on whether training in higher education permeates the possibilities of social transformation; Understand what they think of political formation in higher education and; Discuss which elements are identified by students who contribute to their conception of political formation. The study addressed the phenomena of the university; teacher training; teacher training in Physical Education, and political training on the historical perspective; Social; and conceptual, for this, we rely on the reflections of Paulo Freire (1981, 1994, 1996, 2000); Saviani (1996, 1999, 2003, 2009, 2011, 2017), among others. As a methodological support, from the historical-critical theory with contributions-inspirations in Marx on the central theme - political training we used as a research instrument the questionnaire applied to students from the 5th semester of Physical Education Degree at UFRB. We find that from the perspective of the students, political formation has been taking place in the Physical Education course, we have also verified that politicized being or political formation permeates the social commitment of citizens aware of their role in society, understanding their rights and duties, quality in education, teacher training, class enhancement and human transformation